Induced Förster resonance energy transfer by encapsulation of DNA-scaffold based probes inside a plant virus based protein cage. (11th April 2018) - de Ruiter, Mark V; Overeem, Nico J; Singhai, Gaurav; Cornelissen, Jeroen J L M
Abstract: Insight into the assembly and disassembly of viruses can play a crucial role in developing cures for viral diseases. Specialized fluorescent probes can benefit the study of interactions within viruses, especially during cell studies. In this work, we developed a strategy based on Förster resonance energy transfer (FRET) to study the assembly of viruses without labeling the exterior of viruses. Instead, we exploit their encapsulation of nucleic cargo, using three different fluorescent ATTO dyes linked to single-stranded DNA oligomers, which are hybridised to a longer DNA strand. FRET is induced upon assembly of the cowpea chlorotic mottle virus, which forms monodisperse icosahedral particles of about 22 nm, thereby increasing the FRET efficiency by a factor of 8. Additionally, encapsulation of the dyes in virus-like particles induces a two-step FRET. When the formed constructs are disassembled, this FRET signal is fully reduced to the value before encapsulation. This reversible behavior makes the system a good probe for studying viral assembly and disassembly. It, furthermore, shows that multi-component supramolecular materials are stabilized in the confinement of a protein cage.